Areal of Microtus arvalis in Mountain Dagestan - F. M. Abdulaeva; Ch. M. Ramazanov (Юг России: экология, развитие)
On the article regards the areal of Microtus arvalis in the mountain Dagestan. 5 groups of population of Microtus arvalis are picked out. The settlements of Microtus arvalis meet from the zone of alpine meadows.